A Proposed Employee Development Program from Objectives and Key Results: A Case Study of SG Group of Companies - Charoenlarpkul, Chayapol; Tantasanee, Somchai (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
Nowadays, many organizations have to re-think about strategic management more than in the past to face with the situation which every resources and abilities could be calculated as exact number to gain the best profit for organization. Investment in human resources has become a very large topic within the business world, so employee development become a necessary factor which the organization must focus on as it affects to organization performance directly. Performance Appraisal or Performance Evaluation System which is one of the most necessary tools to improve human assets became the core issue of the discussion. The purpose of the study was to propose Employee Development Program using the concept of “Objective & Key Result (OKR)”. Quantitative data using questionnaires was obtained from 93 respondents at Power Plant Section by using purposive sampling method. The result indicated that only Organization Direction has a statistically significant influence on Work Performance. Thus, Organization Direction is the most effective factor that has a significant influence on Work Performance based on OKR concept. Even though the statistical analysis showed that only Organization Direction has a significant influence on Work Performance, interview statements demonstrated that all of elements within OKR have significant influence on Work Performance as well. Thus, all the element in OKR still should be considered, but the organization might focus on the Organization Direction as the first priority.